CXCL12/CXCR4 signaling counteracts docetaxel-induced microtubule stabilization via p21-activated kinase 4-dependent activation of LIM domain kinase 1 - Bhardwaj, Arun (Oncotarget, 2014)
Emerging data highlight the significance of chemokine (C-X-C motif) ligand 12/chemokine (C-X-C motif) receptor 4 (CXCL12/CXCR4) signaling axis in the chemoresistance of several malignancies, including prostate cancer (PCa); however, underlying mechanisms remain largely elusive. Here, we demonstrate that CXCL12 treatment rescues the PCa cells from docetaxel (DTX)-induced toxicity by overriding its effect on cell cycle (G(2)/M phase arrest). We further demonstrate that the chemoprotective effect of CXCL12 is abolished upon pharmacological inhibition or RNA interference-mediated silencing of CXCR4. Moreover, microtubule stabilization caused by DTX is suppressed in CXCL12-stimulated PCa cells as revealed by immunofluorescence and immunoblot analyses. The effect of CXCL12 on microtubule stabilization is abrogated when PCa cells are pre-treated with a CXCR4 antagonist. In additional studies, we show that the chemoprotective action of CXCL12/CXCR4 signaling is mediated by p21-activated kinase 4 (PAK4)-dependent activation of Lim domain kinase 1 (LIMK1), and inhibition of either PAK4 or LIMK1 leads to re-sensitization of PCa cells to DTX-induced tubulin polymerization and cellular toxicity even in the presence of CXCL12. Altogether, our findings uncover a novel mechanism underlying CXCL12/CXCR4 signaling-induced PCa chemoresistance and suggest that targeting of this signaling axis or its downstream effector pathway could lead to therapeutic enhancement of DTX.